2017
DOI: 10.1038/srep44277
|View full text |Cite|
|
Sign up to set email alerts
|

New insights into the intracellular distribution pattern of cationic amphiphilic drugs

Abstract: Cationic amphiphilic drugs (CADs) comprise a wide variety of different substance classes such as antidepressants, antipsychotics, and antiarrhythmics. It is well recognized that CADs accumulate in certain intracellular compartments leading to specific morphological changes of cells. So far, no adequate technique exists allowing for ultrastructural analysis of CAD in intact cells. Azidobupramine, a recently described multifunctional antidepressant analogue, allows for the first time to perform high-resolution s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Finally, all psychotropic compounds with cationic amphiphilic properties caused a significant reduction in ψm. Since oncogenic activation leads to increased mitochondrial metabolism and higher ψm compared to that of noncancer cells (20) and experimental evidence demonstrates that irreversible mitochondrial membrane depolarization can induce cell death also in apoptotic resistant cells (84), CADs appear excellent candidates for mitochondrial targeting in cancer, as they can easily diffuse in tumor tissues and interact with negatively charged mitochondrial membranes (20,45,49). Since in our cell line model cytotoxicity of psychotropic drugs was not mediated by ROS and thiols oxidation whereas apoptosis has been demonstrated only in cells treated with spiperone, studies are underway to explore the molecular mechanisms underlying CADs induced mitochondrial membrane depolarization and its role in inducing cancer cell death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, all psychotropic compounds with cationic amphiphilic properties caused a significant reduction in ψm. Since oncogenic activation leads to increased mitochondrial metabolism and higher ψm compared to that of noncancer cells (20) and experimental evidence demonstrates that irreversible mitochondrial membrane depolarization can induce cell death also in apoptotic resistant cells (84), CADs appear excellent candidates for mitochondrial targeting in cancer, as they can easily diffuse in tumor tissues and interact with negatively charged mitochondrial membranes (20,45,49). Since in our cell line model cytotoxicity of psychotropic drugs was not mediated by ROS and thiols oxidation whereas apoptosis has been demonstrated only in cells treated with spiperone, studies are underway to explore the molecular mechanisms underlying CADs induced mitochondrial membrane depolarization and its role in inducing cancer cell death.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds contain both a hydrophobic and a hydrophilic domain; the hydrophobic domain contains one or more aromatic rings whereas the hydrophilic part contains a functional amine group that can be ionized (43). CADs family comprises a broad spectrum of compound classes, including dozens of approved drugs that are used to treat a wide range of diseases including allergies, heart diseases, and psychiatric disorders (44,45). Since the antitumoral activity of compounds investigated in this study is not apparently related to their conventional pharmacological properties and clinical use, we investigated the CADs properties of psychotropic drugs used in our screening evaluating their chemical structure, logP and pKa in comparison to the wellknown CADs compounds amiodarone, chlorpromazine and chloroquine ( Supplementary Table 2) (46,47).…”
Section: Psychotropic Drugs With Significant Antitumoral Activity Dismentioning
confidence: 99%
See 1 more Smart Citation
“…Given the multitude of the cellular effects of antidepressants beyond monoaminergic neurotransmission, and the plethora of at least partially redundant autophagy proteins [9], it will be challenging to pinpoint the exact mechanisms that evoke the autophagic response. Their characteristic as cationic amphiphilic chemicals might play a role [61,64], and new tools to decipher novel molecules directly interacting with antidepressants should also contribute to elucidating their molecular mode of action [64,65].…”
Section: Autophagy In the Action Of Antidepressantsmentioning
confidence: 99%
“…Moreover, it is also reported that for a cationic amphiphilic base, its intracellular distribution pattern also strongly depends on drug concentration and exposure time because the induction of phospholipidosis in tissues increases the production of AP in the biological membranes for a greater membrane accumulation and tissue distribution. 45 In this case, their partitioning into the membranes might become even more important compared to n-octanol. This aspect would also need to be added in the TCM to predict tissue partitioning over time for this specific class of drugs.…”
Section: Discussionmentioning
confidence: 99%